The subharmonic amplitude of SonoVue increases with hydrostatic pressure at low incident acoustic pressures - Nio, A; Faraci, A; Christensen-Jeffries, K; Eckersley, R; Monaghan, M; Raymond, J; Forsberg, F; Lamata, P (Institute of Electronics and Electrical Engineers, 2017)
Physiologically important pressures in the heart and aorta are currently assessed with invasive pressure catheters. The subharmonic signal from microbubble ultrasound contrast agents, however, may be exploited to estimate pressures non-invasively. The objective of this work was (i) to develop a static phantom from commercially-available components for easy replication across different laboratories, and (ii) to investigate the subharmonic response of the ultrasound contrast agent SonoVue (Bracco Spa, Milan, Italy) at physiological pressures within this phantom. A phantom capable of maintaining 0-200 mmHg static pressures was developed using a cell culture cassette with Luer connections. SonoVue was added (0.4 μL/mL) and radiofrequency data were recorded on the ULtrasound Advanced Open Platform (ULA-OP) from 3.5-100% scanner acoustic output levels (transmit frequency 5 MHz, 16-cycle pulse, pulse-inversion). Signal processing was performed to extract the mean subharmonic amplitude in a 1 MHz bandwidth (2-3 MHz). A single growth phase between 75-325 kPa peak-to-peak acoustic pressures was observed at ambient pressure (0 mmHg). Within this growth phase, SonoVue exhibited an increase in subharmonic amplitude from 0-75 mmHg hydrostatic pressure, a plateau between 75-125 mmHg, and a decrease from 125-200 mmHg. The maximum sensitivity of SonoVue to hydrostatic pressure up to 75 mmHg was observed at 152 kPa peak-to-peak acoustic pressure (0.13 dB/mmHg, r2=0.99). This increase in subharmonic signal could have arisen from compression-only behavior as predicted by the Marmottant model, and may have clinical applications in estimating diastolic pressures non-invasively.